[Qing dai xing fa ji lu. Diao xing = Crime and punishment under the Qing dynasty. Suspension]. ([China?] : [publisher not identified], 1850)
A original gouache paintings showing the traditional criminal punishments used in Qing dynasty. Chinese criminal justice: suspension.
Original painting on pith paper.
Part of the collection: Qing dai xing fa ji lu = Crime and punishment under the Qing dynasty, 1850-1860?
Title devised by cataloguer based on the image.
Also available online
Keywords: China trade watercolor painting; Watercolor painting, Chinese -- 19th century; Punishment -- China -- Pictorial works